THE ROLE OF MODERN COMPUTER TECHNOLOGIES AND ARTIFICIAL INTELLIGENCE IN THE FIELD OF ENDOCRINOLOGY - Ataxanov Sanjarbek Anvarovich; Ismoilova Madina Axrorjon qizi (Bright Mind Publishing, 2025)
In recent years, the field of endocrinology has gained significant attention and development not only in Uzbekistan but also worldwide. This article highlights the role of information technology (IT) and artificial intelligence (AI) in endocrinology, emphasizing their use in diagnostics, treatment, and disease prediction. Disorders of the endocrine system—such as diabetes mellitus, thyroid dysfunction, and hormone-related imbalances—are complex conditions that require an individualized approach. This paper analyzes the possibilities of using AI-based systems to monitor and evaluate patients’ conditions, control hormone levels, and create personalized treatment plans. In addition, it examines the benefits and advantages of electronic medical records, mobile applications, and cloud technologies in endocrinological practice. The article provides practical recommendations and an analytical overview of the opportunities offered by modern technologies for specialists and researchers in endocrinology.
Keywords: endocrinology, information technologies, artificial intelligence, diagnostics, hormones, electronic medical records, diabetes mellitus, thyroid diseases, cloud technologies, mobile applications